Pemberdayaan Masyarakat Dalam Upaya Peningkatan Kualitas Desa Wisata Berbasis Budaya Dan Teknologi Di Desa Wisata Karanggayam - Halim Qista Karima; Dina Rachmawaty; Muhammad Afrizal Amrustian (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The growth of tourist villages in Kebumen has created increasingly fierce competition. Competition supported by good management can improve the quality of tourist destinations. A strategy is needed in competition to improve the quality of Tourism Villages. Karanggayam Tourism Village is one of the tourist villages in Kebumen. To improve the quality of this destination is needed to increase the number of visitors and community participation in managing the Tourism Village. Community Service Program as an effort to improve the quality of Tourism Villages by prioritizing the 4A aspects of Attraction, Accessibility, Amenities, and Ancillary. Program implementation is based on the Plan Do Check Action (PDCA) concept. This technique can increase the number of visitors and community participation by 25%. The sustainability of the Tourism Village is carried out with support and collaboration between levels of society.